Whole-Genome Epidemiology and Characterization of Methicillin-Susceptible Staphylococcus aureus ST398 From Retail Pork and Bulk Tank Milk in Shandong, China - Zhao, Xiaonan; Hu, Ming; Zhao, Cui; Zhang, Qing; Li, Lulu; Zhang, Yin; Luo, Yanbo; Liu, Yuqing (Frontiers in Microbiology, 2021)
Staphylococcus aureus (S. aureus) is now regarded as a zoonotic agent. Methicillin-susceptible S. aureus (MSSA) ST398 is a livestock-associated bacterium that is most prevalent in China, but there are currently no data available for Shandong. Therefore, the aim of this study was to investigate the epidemiology and characterization of MSSA ST398 from retail pork and bulk tank milk (BTM) in Shandong. A total of 67 S. aureus isolates were collected from retail pork between November 2017 and June 2018. Among the isolates, high antimicrobial resistance rates were observed for penicillin (97.0%), and 92.5% of the isolates were multi-drug resistant (MDR). Eight sequence types (STs) were identified in the retail pork isolates, and the predominant type was ST15 (n=26), which was followed by ST398 (n=14). Staphylococcal protein A gene (spa) typing identified spa types t034 and t1255 in MSSA ST398 from retail pork. Using whole-genome sequencing analysis, we described the phylogeny of 29 MSSA ST398 isolates that were obtained from retail pork (n=14) and BTM (n=15). The phylogenetic tree showed that the MSSA ST398 isolates from different sources had the same lineage. Among the 29 MSSA ST398 isolates, five resistance genes were detected, and all isolates carried DHA-1. Fifteen toxin genes were detected, and all isolates carried eta, hla, and hlb. In conclusion, this study found that a high risk for MSSA ST398 was present in retail pork and BTM. These findings have major implications for how investigations of MSSA ST398 outbreaks should be conducted in the One-Health context.